A note on linear complementarity problems and multiple objective programming - Mohan, S.R.; Neogy, S.K.; Das, A.K. (Mathematical programming, 2004)
Kostreva and Wiecek [3] introduced a problem called LCP-related weighted problem in connection with a multiple objective programming problem, and suggested that a given linear complementarity problem (LCP) can be solved by solving the LCP-related weighted problem associated with it. In this note we provide several clarifications of the claims made in [3]. Finally, we feel that solving any LCP by the approach given in [3] may not be as useful as it is claimed. [PUBLICATION ABSTRACT]